Selected Thiadiazine-Thione Derivatives Attenuate Neuroinflammation in Chronic Constriction Injury Induced Neuropathy - Qureshi, Sonia; Ali, Gowhar; Idrees, Muhammad; Muhammad, Tahir; Kong, Il-Keun; Abbas, Muzaffar; Shah, Muhammad Ishaq Ali; Ahmad, Sajjad; Sewell, Robert D. E.; Ullah, Sami (Frontiers in Molecular Neuroscience, 2021)
Neuropathic pain refers to a lesion or disease of peripheral and/or central somatosensory neurons and is an important body response to actual or potential nerve damage. We investigated the therapeutic potential of two thiadiazine-thione [TDT] derivatives, 2-(5-propyl-6-thioxo-1, 3, 5-thiadiazinan-3-yl) acetic acid [TDT1] and 2-(5-propyl-2-thioxo-1, 3, 5-thiadiazinan-3-yl) acetic acid [TDT2] against CCI (chronic constriction injury)-induced neuroinflammation and neuropathic pain. Mice were used for assessment of acute toxicity of TDT derivatives and no major toxic/bizarre responses were observed. Anti-inflammatory activity was assessed using the carrageenan test, and both TDT1 and TDT2 significantly reduced carrageenan-induced inflammation. We also used rats for the induction of CCI and performed allodynia and hyperalgesia-related behavioral tests followed by biochemical and morphological analysis using RT-qPCR, immunoblotting, immunohistochemistry and immunofluorescence. Our findings revealed that CCI induced clear-cut allodynia and hyperalgesia which was reversed by TDT1 and TDT2. To determine the function of TDT1 and TDT2 in glia-mediated neuroinflammation, Iba1 mRNA and protein levels were measured in spinal cord tissue sections from various experimental groups. Interestingly, TDT1 and TDT2 substantially reduced the mRNA expression and protein level of Iba1, implying that TDT1 and TDT2 may mitigate CCI-induced astrogliosis. In silico molecular docking studies predicted that both compounds had an effective binding affinity for TNF-α and COX-2. The compounds interactions with the proteins were dominated by both hydrogen bonding and van der Waals interactions. Overall, these results suggest that TDT1 and TDT2 exert their neuroprotective and analgesic potentials by ameliorating CCI-induced allodynia, hyperalgesia, neuroinflammation and neuronal degeneration in a dose-dependent manner.